2007
DOI: 10.1051/apido:2007040
|View full text |Cite
|
Sign up to set email alerts
|

Honey bee colonies that have survivedVarroa destructor

Abstract: -We document the ability of a population of honey bee colonies to survive in France without Varroa suppression measures. We compared the mortality of collected Varroa surviving bee (VSB) stock with that of miticide-treated Varroa-susceptible colonies. Varroa infestation did not induce mortality in the VSB colonies. Some of the original colonies survived more than 11 years without treatment and the average survival of the experimental colonies was 6.54 ± 0.25 years. Swarming was variable (41.50 ± 9.94%) dependi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
134
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(136 citation statements)
references
References 18 publications
1
134
0
1
Order By: Relevance
“…In particular, colonies headed by queens descending from "survivor stock" (Le Conte et al, 2007) Likewise, no significant differences in disease occurrence between local and non-local experimental colonies were observed. Clearly, both local and non-local honey bees become infected and suffer from dis-…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In particular, colonies headed by queens descending from "survivor stock" (Le Conte et al, 2007) Likewise, no significant differences in disease occurrence between local and non-local experimental colonies were observed. Clearly, both local and non-local honey bees become infected and suffer from dis-…”
Section: Discussionmentioning
confidence: 94%
“…(Behrens et al, 2007;Jensen et al, 2009;Huang et al, 2013). The existence of several local strains of bee that have survived under V. destructor infestation pressure in the absence of treatment and which apparently possess strategies to limit mite population growth have been reported (Fries et al, 2006;Le Conte et al, 2007;Seeley, 2007), and "varroa tolerant" honey bee strains have been reported from several locations (Koeniger et al, 1995;Kefuss et al, 2004;Harbo and Harris, 2005;Rinderer et al, 2010). reason, we agreed on a standard sampling from the colony periphery that was always possible.…”
Section: Samplingmentioning
confidence: 99%
“…Even small subpopulations of European races have been well documented as surviving with uncontrolled Varroa mite infestation for a decade or longer (De Jong and Soares 1997;Fries et al 2006;Le Conte et al 2007;Rinderer et al 2001;Seeley 2007). These populations of A. mellifera honeybees surviving Varroa mites may reveal genetic and ecological factors that enable mite resistance including important mite-resistant traits that could be adopted in breeding programs.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, beekeepers in most countries have to treat their colonies annually to ensure their survival (Rosenkranz et al 2010). However, some honeybee populations survive mite infestations without chemical treatment (De Jong and Soares, 1997;Kefuss et al 2004;Fries et al 2006;Le Conte et al 2007;Seeley 2007;Locke and Fries, 2011;Locke et al 2012;Seeley et al 2015). It is not yet clear whether their survival is due to tolerance that limits the detrimental effects of parasitism on the host or exclusively to resistance mechanisms reducing the fitness of the parasites (Råberg et al 2007(Råberg et al , 2009).…”
Section: Introductionmentioning
confidence: 99%